2003
DOI: 10.1183/09031936.03.00042702
|View full text |Cite
|
Sign up to set email alerts
|

Increased tumour necrosis factor‐α plasma levels during moderate-intensity exercise in COPD patients

Abstract: Post-training downregulation of muscle tumour necrosis factor (TNF)-a messenger ribonucleic acid (mRNA) expression and decrease in cellular TNF-a levels have been reported in the elderly. It is hypothesised that chronic obstructive pulmonary disease (COPD) patients may not show these adaptations due to their reduced ability to increase muscle antioxidant capacity with training.Eleven COPD patients (forced expiratory volume in one second 40¡4.4% of the predicted value) and six age-matched controls were studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
119
5
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(147 citation statements)
references
References 32 publications
13
119
5
10
Order By: Relevance
“…This is in agreement with the findings reported by RABINOVICH et al [27], who studied nine patients and six healthy controls and found that at rest, TNF-a mRNA expression was significantly higher in the COPD patients.…”
Section: Discussionsupporting
confidence: 83%
“…This is in agreement with the findings reported by RABINOVICH et al [27], who studied nine patients and six healthy controls and found that at rest, TNF-a mRNA expression was significantly higher in the COPD patients.…”
Section: Discussionsupporting
confidence: 83%
“…However, other studies, with more consistence methodology, perceived this difference [2,32]. As opposed to the present study, it was verified in COPD individuals and increase in TNF-α plasma levels after eleven minutes of moderate intensity ergometric exercise [8]. The present study, in turn, although the mean was numerically higher after 6MWT in COPD group, verified no significant difference.…”
Section: Discussioncontrasting
confidence: 54%
“…To be able to detect a 10% difference or higher between the means of both groups, regarding the utilization of a proportion of 1 control to 2 individuals with COPD commonly employed in the literature [8], the sample calculation showed the need to include 17 individuals in the COPD group and 8 individuals in the control group. It was decided to include 20% more individuals in the COPD group due to the risk of losses throughout the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, systemic blood concentrations of tumor necrosis factor (TNF)-α, IL 6, IL 8, CRP and fi brinogen are higher in COPD than in control subjects (Gan et al 2004). Interestingly, at variance from the response observed in healthy subjects and diabetic patients, moderate-intensity exercise abnormally increases plasma TNF-α levels in COPD patients (Rabinovich et al 2003;Zoppini et al 2006). Circulating TNF-α levels have been found to increase in malnourished COPD patients, likely because systemic hypoxia stimulates TNF-α synthesis (Takabatake et al 2000).…”
Section: Systemic Infl Ammation (Table 1)mentioning
confidence: 95%